If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 3y = 9 Solving -9x + 3y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -9x + 3y + -3y = 9 + -3y Combine like terms: 3y + -3y = 0 -9x + 0 = 9 + -3y -9x = 9 + -3y Divide each side by '-9'. x = -1 + 0.3333333333y Simplifying x = -1 + 0.3333333333y
| -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x | | 2x+6/x+3 | | 25X+6-27X=5-9 | | 3(z-2)=2(z+7) | | -7(3n+2)=-8n+38 | | 7+36=-11 | | 10x-12y=2 | | 5.3m-6=-27.2 | | 5y+6=4y-7 | | .16(12)+.04x=.08(24+x) | | n-4-9=0 | | 2.3f=9.2 | | -4y+-12=2y-14 | | -9(x-1)=9-9x |